Childhood urticaria and angioedema: Pathogenesis, diagnosis and therapy [Çocukluk çaǧında ürtiker ve anjiyoödem: Patojenez, tanı ve tedavi] - BARIŞ, SAFA (Kare Publishing, 2012)
Urticarial disease is characterized by transient erythematous, swelling and pruritic lesions. Classification of the disease as acute and chronic urticeria provide a comprehensive approach to detect the etiological factors and estimate the prognosis. In this paper, clinical classification of urticeria, pathogenesis, related factors with disease and therapy options were reviewed. © Galenos Yayi{dotless}nevi.
Keywords: Angioedema; Child; Urticeria